MORAL VALUE AFFECTION TO CHILD CULTURE DEVELOPMENT USING CHARLES PERRAULT'S “LITTLE RED RIDING HOOD” - Alza Octa Priargiansyah (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Children's culture is important for their growth and development since it teaches them about habits, conduct, and way of life. Fairy tales can be useful in this regard. Fairy tales and the construction of children's culture have a deep connection because fairy tales contain an essential component that can aid in the formation of children's culture, namely moral values. It is intended that by using the moral message, children will learn the values of life, which will influence the formation of habits and behaviors. The researcher is interested in learning how the moral values of Charles Perrault's fairy tale, Little Red Riding Hood, affect children's cultural development. The Reader-response theory was used in this study, which lead to the outcome. By applying the moral value in life would affect the growth of the children's habits and personalities, which is affecting their insight of life so participants would be more prepared for facing any problems that came into their life and that will make participants' lives better and happier.